ANTIOXIDANT PROTECTION SYSTEM OF DOG ORGANISM AT EXPERIMENTAL TOXOCARIASIS - Said, W.; Stybel, V.; Gutyj, B.; Prijma, O. (Scientific Progress & Innovations, 2020)
Processes involving oxygen are constantly taking place in the animal body. They include, in particular, free radical peroxide lipid oxidation. The intensity of free radical processes in the organism depends on the concentration of oxygen in the tissues, as well as the activity of enzymatic and non-enzymatic protection systems. That is why the aim of the study was to determine the state of the antioxidant protection system of dogs in case of experimental toxocariasis. Twelve two- to four-month-old dogs were used for experimental studies. 2 groups of animals, 6 in each were formed: control and experimental. Puppies of the experimental group were experimentally infected with toxocariasis pathogen at a dose of 5,000 invasive eggs of Toxocara canis per kg of body weight. The control puppies were clinically healthy. On the basis of the conducted researches, it been established that at experimental dog toxocariasis their antioxidant status decreases and processes of lipid peroxidation strengthen. The development dog toxocariasis was accompanied by inhibiting all parts of the animals’ antioxidant protection system, as it was indicated by decreasing catalase activity, superoxide dismutase and glutathione system indices in their blood. It was found that in case of toxocariasis invasion on the 15th and 20th days of the experiment, catalase activity in the dog blood decreased by 27.8 and 35.3 % as compared with the control group. On the 15th and 20th day of the experiment, a decrease in the activity of glutathione peroxidase by 14.1 and 18.4 % and glutathione reductase – by 8.3 and 14.5 % were registered in the dog serum of the experimental group. Superoxide dismutase activity was the lowest in the dog blood of the experimental group on the 25th and 30th day of the experiment, this index decreased by 29.1 and 34.4 %, respectively in comparison with the control group. It was found that on the 15th day of the experiment the level of reduced glutathione in the dog blood of the experimental group probably decreased by 11.6 %, and on the 20th day, it decreased by 20.0 % relative to the control group. Against the background of reduced antioxidant status of infected dogs, there was also an increase in the processes of lipid peroxidation, as indicated by an increase in the content of intermediate and final LPO products in their blood: diene conjugates and TBA-active products. Excessive free radical formation and activation of LPO processes led to disruption of cell membrane structure and toxic effects on tissues, as well as oxidation of protein sulfhydryl groups.